ANTIOXIDANT AND ANTIBACTERIAL ACTIVITY TESTS OF BANGKAL LEAF (Nauclea subdita Leaf.) SERUM EXTRACTS - Ika Buana Januarti; Andre Yanto; Cahya Monica (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Bangkal leaves contain polyphenols, alkaloids, flavonoids, and quinone compounds that have the potential to act as antioxidants and antibacterial agents. To maximize the use of bangkal leaves, a cosmetic preparation, serum, was prepared. Serum is composed of 3 formulas: formula 1 (3% extract concentration), formula 2 (4% extract), and formula 3 (5% extract). Serum was tested for antioxidant activity using the DPPH (2,2-Diphenyl-1-Picrylhydrazyl) method at a wavelength of 518 nm. Ascorbic acid was used for comparison. Serum was also tested to evaluate its physical properties including organoleptics, pH, spreadability and viscosity. Antibacterial activity was determined using the well diffusion method. The research results showed that the IC50 value of the extract was 171.18 ppm, the bangkal leaf extract serum preparation for formula I was 174.26 ppm, formula II was 209.97 ppm, and formula III was 237.91 ppm. The antibacterial activity of bangkal leaf extract serum (Nauclea subdita) against Staphylococcus aureus formulas 1, 2, and 3 had an average zone of inhibition of 10.67, 12.00, and 14 mm. Based on the antioxidant and antibacterial activity values, bangkal leaf extract serum has moderate antioxidant and antibacterial abilities. Keywords : Bangkal leaf extract, antioxidant activity test, antibacterial test